Scandium-doped nickel-zinc-cobalt ferrite and preparation method thereof

By using muddy mixing and replacing Fe3+ions in Niznco's iron oxygen, the micro -structure of the material is adjusted to solve the problem of lack of performance in the high -frequency range of the existing materials. The effect of loss is suitable for high -frequency electronic components.

CN115331908BActive Publication Date: 2025-01-28CHENGDU UNIV OF INFORMATION TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210984228.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-17
Publication Date
2025-01-28
Estimated Expiration
2042-08-17

AI Technical Summary

Technical Problem

It is difficult for existing NiZnCo ferrite materials to maintain high magnetic permeability, dielectric constant and saturation magnetization at the same time in the high frequency range, and cannot meet the material requirements of high-frequency electronic products such as 5G technology.

Method used

By using the rare earth element as a doping agent, prepare a doped nickel-zinc and cobalt iron oxygen body, SC3+ions replace the Fe3+ion, and use the Sol-Gel self-spread powder system to combine the solid-phase sintering method to adjust the micro structure and the material of the material and the micro structure and the material of the material and the micro structure and the material of the material and the micro structure and the material of the material and the micro structure and the material of the material and the micro-structure and the material of the material and the micro structure and the material of the material and the micro structure and the micro-structures and the material of the material and the micro structure and the micro-structure and the material of the material. Ion distribution.

Benefits of technology

The material of the material, high magnetic guidance, high saturation magnetization strength, and low medium loss are achieved, and it is suitable for the production of high -frequency electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115331908B_ABST
    Figure CN115331908B_ABST
Patent Text Reader

Abstract

The present invention relates to scandium-doped nickel-zinc-cobalt ferrite and a preparation method thereof, belonging to the technical field of soft ferrite materials. The scandium-doped nickel-zinc-cobalt ferrite has a molecular formula of: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2‑x O4; wherein 0<x≤0.1. The scandium-doped nickel-zinc-cobalt ferrite prepared by the present invention has higher saturation magnetization intensity and higher initial magnetic permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft ferrite materials, in particular to scandium-doped nickel-zinc-cobalt ferrite and a preparation method thereof. Background Art

[0002] NiZnCo ferrite is a common soft magnetic material. Its operating frequency is as high as 1MHz and it has high saturation magnetization Ms, low dielectric loss tanδ and high initial permeability u. i And its low processing cost, low eddy current and low magnetic loss and other unique characteristics provide unique advantages for microwave equipment in the high-frequency field, and it has important applications in components such as inductors, capacitors, and filters. In addition, due to its good biocompatibility and low toxicity, ferrite can be used to manufacture nuclear magnetic resonance contrast agents and drug targeting by using its superparamagnetism and dispersibility. However, with the development and maturity of 5G technology, the integration of various electronic products is getting higher and higher, and the operating frequency is also getting higher and higher. The material requirements for manufacturing high-frequency devices in a wide frequency range are also getting higher and higher. In order to maintain a relatively large magnetic permeability, dielectric constant and high saturation magnetization intensity in a wide frequency range, researchers need to study new ion doping to improve the performance of NiZnCo ferrite. The performance of ferrite is highly dependent on its microstructure and ion distribution. NiZnCo ferrite has a spinel structure. The octahedral point in its crystal structure is represented by [B], and the tetrahedral point is represented by [A]. The distribution of metal ions at the [A] and [B] sites determines the electrical and magnetic properties of NiZnCo ferrites. Substitution with different cations can lead to changes in the lattice constant and the distribution of cations at the [A] and [B] sites, thereby improving the dielectric and magnetic properties. Transition metals and rare earth metals can be used as substitutes to adjust the properties of ferrites. The present invention uses the rare earth element scandium as a dopant to prepare scandium-doped nickel-zinc-cobalt ferrite. The outer electron structure of the scandium atom is 3d14s2, and there is an unpaired electron. It exhibits paramagnetism but has a very low magnetic susceptibility. It is a weakly magnetic material, Sc 3+The number of electrons in the 3d and 4s orbitals of the ion is 0, and the inner electrons are fully filled, so no magnetic moment is shown to the outside. Compared with yttrium atoms in the same group ⅢB, scandium atoms have smaller atomic radius, smaller density, larger atomic weight, higher conductivity and melting point. It is worth noting that the symmetry of the first Brillouin zone of scandium is worse than that of ytterbium. The energy band structure of scandium is more complex, more difficult to calculate, and more unfavorable to enter the substitution position. Therefore, compared with ytterbium ions, scandium ions are less likely to replace other ions. In addition, scandium will form a passivation layer on the surface in nitric acid. The above reasons have led to the use of scandium to dope NiZnCo ferrite, which has higher requirements for the manufacturing process and greater manufacturing difficulty. This is also the reason why many researchers are reluctant to use scandium doping. Not only does the stirring time need to be extended to make the gel more uniform, but the passivation layer on the scandium surface must also be crushed through long-term grinding. In the subsequent sintering process, because sintering time that is too long or too short will affect the performance, the control of sintering time requires trial sintering with many different sintering times to determine which sintering time is more suitable. However, compared with yttrium doping, the NiZnCo ferrite obtained by scandium doping has a higher saturation magnetization and higher initial magnetic permeability, and is more suitable for the production of various electronic components.

[0003] Based on this, a method of using the rare earth element scandium as a dopant and adding a variety of additives to prepare nickel-zinc-cobalt ferrite with high magnetic permeability and high saturation magnetization intensity was studied and designed. Summary of the invention

[0004] The technical problem solved by the present invention is to provide a scandium-doped nickel-zinc-cobalt ferrite, which has higher saturation magnetization intensity and higher initial magnetic permeability and is more suitable for the production of various electronic components.

[0005] The scandium-doped nickel-zinc-cobalt ferrite of the present invention has the molecular formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where 0<x≤0.1.

[0006] In one embodiment, 0.025≤x≤0.1.

[0007] As a preferred embodiment, x=0.025, 0.05, 0.075 or 0.1.

[0008] The present invention provides a method for preparing scandium-doped nickel-zinc-cobalt ferrite.

[0009] The method for preparing scandium-doped nickel-zinc-cobalt ferrite comprises the following steps:

[0010] a. Prepare a wet gel precursor: mix nickel salt, zinc salt, cobalt salt, iron salt, scandium salt and water, add citric acid after dissolving, stir and react at 70-90° C. for 3-6 hours, and then adjust the pH value to 6.5-7.5 to obtain a wet gel precursor;

[0011] b. Preparing a dry gel precursor: drying the wet gel precursor to obtain a dry gel precursor;

[0012] c. Self-propagating combustion reaction: Use an igniter to ignite the dry gel precursor, which self-propagates into nano-scale powder;

[0013] d. Ball milling: mixing the nano-sized powder with the additive and then ball milling to obtain a ball mill material; wherein the additive is a mixture of CaCO3 and SiO2;

[0014] e. Granulation: After the ball mill is dried, polyvinyl alcohol is added to granulate;

[0015] f. Blank making: the powder after granulation is pressed into blanks;

[0016] g. Sintering: Sinter the blank at 1100-1200°C for 2-6 hours to obtain scandium-doped nickel-zinc-cobalt ferrite.

[0017] In one embodiment, in step a, the nickel salt is nickel nitrate, the zinc salt is zinc nitrate, the cobalt salt is cobalt nitrate, the iron salt is iron nitrate, and the scandium salt is scandium nitrate.

[0018] In one embodiment, step a: the ratio of the amount of nickel salt, zinc salt, cobalt salt, iron salt, and scandium salt is 3-5: 2-4: 0.7-0.9: 15-17: 0.15-0.9. Preferably, the ratio of the amount of nickel salt, zinc salt, cobalt salt, iron salt, and scandium salt is 3-5: 2-4: 0.7-0.9: 15-17: 0.7-0.9.

[0019] In one embodiment, in step a, the amount of citric acid added is 2 to 4 times the sum of the amounts of nickel salt, zinc salt, cobalt salt, iron salt and scandium salt; preferably, the amount of citric acid added is 3 times the sum of the amounts of nickel salt, zinc salt, cobalt salt, iron salt and scandium salt.

[0020] Preferably, in step d, the weight ratio of CaCO3 to SiO2 is 0.4-1.6:0.5-1.2.

[0021] Preferably, in step d, CaCO3 and SiO2 are added in a ratio of 17-21:0.4-1.6:0.5-1.2 of the weight ratio of nano-powder, CaCO3 and SiO2.

[0022] Preferably, in step a, the reaction is stirred at 80° C. for 4 h, and then the pH value is adjusted to 7;

[0023] In step b, the drying temperature is 70°C to 90°C; preferably, the drying temperature is 80°C;

[0024] In step c, the ignition agent is alcohol;

[0025] In step d, the ball milling time is 9 to 18 hours, preferably 11 hours;

[0026] In step e, the polyvinyl alcohol is a polyvinyl alcohol aqueous solution; preferably, the concentration of the polyvinyl alcohol aqueous solution is 6wt% to 12wt%; the amount of the polyvinyl alcohol aqueous solution is determined according to the weight ratio of the nano-powder to the polyvinyl alcohol of 0.3 to 0.7:0.2 to 0.5

[0027] In step f, the pressing pressure is 5 to 20 MPa, and the pressing time is 0.5 to 2 min; preferably, the pressing pressure is 10 MPa, and the pressing time is 1 min;

[0028] In step g, the blank is sintered at 1150° C. for 4 h.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1) In this technical solution, the Sol-gel self-propagating powder preparation method combined with the solid phase sintering method is used to prepare NZCSF ferrite soft magnetic material, and rare earth Sc3+ ions are used instead of Fe3+ ions to prepare soft magnetic ferrite materials with excellent electromagnetic properties, high saturation magnetization intensity and high initial magnetic permeability, which has a wide range of application scenarios.

[0031] 2) The NZCSF ferrite soft magnetic material prepared in the present technical scheme is added with Sc3+ ions. Due to the large radius of Sc3+, the original ion distribution of NiZnCo ferrite is affected, and the grain size of NiZnCo ferrite is refined, so that it has good electromagnetic properties. In the present technical scheme, the electromagnetic properties of the NiZnCo ferrite material can be improved and the saturation magnetization of the material can be effectively improved by changing the microscopic morphology of the material and replacing the non-magnetic ions with rare earth ions. Therefore, the preparation of soft magnetic ferrite materials with excellent electromagnetic properties and high saturation magnetization by replacing Fe3+ ions in NiZnCo ferrite with rare earth ions has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The X-ray diffraction patterns of the NZCSF ferrite materials prepared in Examples 1-4 and Comparative Example 1 are shown.

[0033] Figure 2 middle, Figure 2 (a) is a graph showing the relationship between the dielectric constant of the NZCSF ferrite materials prepared in Examples 1-4 and Comparative Example 1 and the frequency; Figure 2 (b) is the relationship between dielectric loss and frequency; Figure 2 (c) is a graph showing the relationship between resistance and temperature.

[0034] Figure 3 middle, Figure 3 (a) is a hysteresis loop diagram of the NZCSF ferrite material prepared in Examples 1-4 and Comparative Example 1;

[0035] Figure 3 (b) is a data graph showing the variation of saturation magnetization and coercive force with the scandium substitution amount x. Figure 3 (c) is the relationship between the magnetic permeability and the frequency; Figure 3 (d) is the relationship between magnetic loss and frequency. DETAILED DESCRIPTION

[0036] The scandium-doped nickel-zinc-cobalt ferrite of the present invention has the molecular formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, wherein 0<x≤0.1. The scandium-doped nickel-zinc-cobalt ferrite of the present invention is based on Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4 ferrite based, Sc 3+ Replace Fe 3+ In order to improve the magnetic and electrical properties of the material, the resulting scandium-doped nickel-zinc-cobalt ferrite has high sintering density, high magnetic permeability, high saturation magnetization, high initial magnetic permeability, high resistivity, low coercive force and low dielectric loss. It can provide key materials for high-frequency inductors and capacitors, and solve the current situation of lack of related electronic components in the high-frequency and weak-current field in China. It is expected to improve my country's core competitiveness in the miniaturization and integration of high-frequency and even ultra-high-frequency electronic devices, and break the foreign technology blockade.

[0037] The scandium-doped nickel-zinc-cobalt ferrite of the present invention has the molecular formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where 0<x≤0.1.

[0038] Preferably, 0.025≤x≤0.1.

[0039] As a preferred embodiment, x=0.025, 0.05, 0.075 or 0.1. That is, the molecular formula of the scandium-doped nickel-zinc-cobalt ferrite is Ni 0.5 Zn 0.4Co 0.1 Sc 0.025 Fe 1.975 O4、Ni 0.5 Zn 0.4 Co 0.1 Sc 0.05 Fe 1.95 O4、Ni 0.5 Zn 0.4 Co 0.1 Sc 0.075 Fe 1.925 O4 or Ni 0.5 Zn 0.4 Co 0.1 Sc 0.1 Fe 1.9 O4.

[0040] The present invention provides a method for preparing scandium-doped nickel-zinc-cobalt ferrite.

[0041] The method for preparing scandium-doped nickel-zinc-cobalt ferrite comprises the following steps:

[0042] a. Prepare a wet gel precursor: mix nickel salt, zinc salt, cobalt salt, iron salt, scandium salt and water, add citric acid after dissolving, stir and react at 70-90° C. for 3-6 hours, and then adjust the pH value to 6.5-7.5 to obtain a wet gel precursor;

[0043] b. Preparing a dry gel precursor: drying the wet gel precursor to obtain a dry gel precursor;

[0044] c. Self-propagating combustion reaction: Use an igniter to ignite the dry gel precursor, which self-propagates into nano-scale powder;

[0045] d. Ball milling: mixing the nano-sized powder with the additive and then ball milling to obtain a ball mill material; wherein the additive is a mixture of CaCO3 and SiO2;

[0046] e. Granulation: After the ball mill is dried, polyvinyl alcohol is added to granulate;

[0047] f. Blank making: the powder after granulation is pressed into blanks;

[0048] g. Sintering: Sinter the blank at 1100-1200°C for 2-6 hours to obtain scandium-doped nickel-zinc-cobalt ferrite.

[0049] The method of the present invention adopts a sol-gel method combined with self-propagating and ball milling to prepare Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-xThe O4 spinel ferrite material has a simple preparation process and a pollution-free process. The obtained material simultaneously obtains a relatively high initial magnetic permeability and saturation magnetization intensity.

[0050] The purpose of step a is to obtain a wet gel precursor. Nickel salt, zinc salt, cobalt salt, iron salt, scandium salt and deionized water are mixed, citric acid is added after dissolution, and the reaction is stirred at 70-90° C. for 3-6 hours, and then the pH value of the system after the reaction is adjusted to 6.5-7.5 to obtain a wet gel precursor.

[0051] The ratio of nickel salt, zinc salt, cobalt salt, iron salt and scandium salt is determined by the molecular formula of the target product. 0.5 Zn 0.4 Co 0.1 Sc 0.025 Fe 1.975 O4, the molar ratio of the metal elements in nickel salt, zinc salt, cobalt salt, scandium salt and iron salt is 0.5:0.4:0.1:0.025:1.975, that is, in molar ratio, Ni:Zn:Co:Sc:Fe=0.5:0.4:0.1:0.025:1.975.

[0052] Preferably, in step a, the ratio of the amount of nickel salt, zinc salt, cobalt salt, iron salt, and scandium salt is 3-5: 2-4: 0.7-0.9: 15-17: 0.15-0.9; more preferably, the ratio of the amount of nickel salt, zinc salt, cobalt salt, iron salt, and scandium salt is 3-5: 2-4: 0.7-0.9: 15-17: 0.7-0.9. Within this range, the scandium-doped nickel-zinc-cobalt ferrite prepared has a ferrite material with higher saturation magnetization and higher initial magnetic permeability.

[0053] Commonly used water-soluble metal salts are suitable for the present invention. Preferably, the nickel salt is nickel nitrate, the zinc salt is zinc nitrate, the cobalt salt is cobalt nitrate, the iron salt is iron nitrate, and the scandium salt is scandium nitrate.

[0054] In order to speed up the mixing and dissolving rate, heating and stirring can also be used during mixing. The present invention has no requirement on the amount of deionized water added during mixing, and it only needs to be able to dissolve the added metal salt.

[0055] After the above metal salts are mixed and dissolved in water, citric acid is added. Preferably, the amount of citric acid added is 2 to 4 times the sum of the amounts of nickel salt, zinc salt, cobalt salt, iron salt and scandium salt. As a preferred embodiment, the amount of citric acid added is 3 times the sum of the amounts of nickel salt, zinc salt, cobalt salt, iron salt and scandium salt.

[0056] After adding citric acid, the temperature is raised, and the reaction is stirred at 70-90°C for 3-6 hours, and then the pH value in the reaction system is adjusted to 6.5-7.5. The methods commonly used in the art for adjusting pH are applicable to the present invention. For example, the pH value of the system can be adjusted by gradually adding ammonia water. As a preferred embodiment, in step a, the reaction is stirred at 80°C for 4 hours, and then the pH value is adjusted to 7.

[0057] The purpose of step b is to obtain a dry gel precursor, and it is only necessary to remove the water in the wet gel precursor obtained in step a. Conventional methods for removing water in the art can be used, such as drying, air-drying, and shade-drying. As a preferred solution, drying is carried out at 70°C to 90°C; preferably, the drying temperature is 80°C.

[0058] Step c: The dry gel precursor is mixed with an igniter and ignited to self-propagate into nano-scale powder, and then polyvinyl alcohol is added to granulate.

[0059] The commonly used igniters in the art are all suitable for the present invention. Preferably, the igniter is alcohol. Only a small amount of alcohol needs to be added, and the amount added is the amount used for conventional ignition in the art, which will not be described in detail here.

[0060] After the self-propagating combustion reaction, the dry gel precursor turns into nano-scale powder;

[0061] The purpose of step d is to fully mix the powder with the additive. The mixing method adopts ball milling, and the ball milling time is 9 to 18 hours, preferably 11 hours. In this step, it is necessary to add a combined additive of CaCO3 and SiO2. If no combined additive is added or only CaCO3 or SiO2 is added, the product performance will be seriously affected. In one embodiment, the weight ratio of CaCO3 to SiO2 is 0.4 to 1.6:0.5 to 1.2; preferably, in step d, the amount of CaCO3 and SiO2 is added according to the weight ratio of nano-powder, CaCO3 and SiO2 of 17 to 21:0.4 to 1.6:0.5 to 1.2.

[0062] In step e, the nanopowder is mixed with polyvinyl alcohol for granulation. Preferably, the polyvinyl alcohol is a polyvinyl alcohol aqueous solution; more preferably, the concentration of the polyvinyl alcohol aqueous solution is 6wt% to 12wt%; the amount of the polyvinyl alcohol aqueous solution is determined according to the weight ratio of the nanopowder to the polyvinyl alcohol of 0.3 to 0.7:0.2 to 0.5.

[0063] Step f is a commonly used pressing method in the art, which is applicable to the present invention. The present invention is to press the powder into sheets and rings. Preferably, the pressing pressure is 5-20 MPa, and the pressing time is 0.5-2 min; more preferably, the pressing pressure is 10 MPa, and the pressing time is 1 min. Pressing can be performed using commonly used equipment, such as a manual hydraulic press.

[0064] Step g is a sintering step, wherein the blank is sintered at 1100-1200° C. for 2-6 hours to obtain scandium-doped nickel-zinc-cobalt ferrite. In a preferred embodiment, the blank is sintered at 1150° C. for 4 hours.

[0065] The specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.

[0066] The purity of the raw materials Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, Co(NO3)2·6H2O, Fe(NO3)3·9H2O and Sc(NO3)3·6H2O used in the examples is greater than 99.9wt%.

[0067] Example 1

[0068] A method for preparing a scandium-doped nickel-zinc-cobalt ferrite soft magnetic material comprises the following steps:

[0069] 1) Ingredients

[0070] Analytical pure Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, Co(NO3) 2, Sc(NO3)3·6H2O and Fe(NO3)3·9H2O are used as raw materials, according to the chemical formula Ni 0.5 Zn 0.4 Co 0.1 Sc 0.025 Fe 1.975 O4 weighs the ingredients.

[0071] 2) Preparation

[0072] a. Preparation of wet gel precursor: Ni 0.5 Zn 0.4 Co 0.1 Sc 0.025 Fe 1.975 O4 dissolves nitrate in deionized water, and then fully mixes and dissolves to form a solution with a concentration of 0.15 mol / L; adds citric acid in a molar ratio of citric acid to nitrate of 3 to the prepared solution, and then seals it, and then magnetically stirs it at 80°C for 4 hours to obtain a clear brown-green precursor solution; after cooling the precursor solution to room temperature, ammonia water is added thereto to adjust its pH value to 7;

[0073] b. Preparing a xerogel precursor: drying a solution having a pH value of 7 at 80° C. to form a xerogel precursor;

[0074] c. Self-propagating combustion reaction: Use alcohol to ignite the dry gel precursor, and generate fluffy dendrites through self-propagating combustion to obtain nano-scale powder;

[0075] d. Ball milling: The obtained nano-scale powder is mixed with additives and put into a ball mill for ball milling; after 11 hours of ball milling, NZCSF ferrite powder is obtained; wherein the additive is a mixture of CaCO3 and SiO2; the amount of CaCO3 and SiO2 is added according to the ratio of nano-scale powder, CaCO3 and SiO2 of 18:1:1.

[0076] e. Granulation: The ball mill is placed in an oven for drying; the obtained NZCSF ferrite nanopowder is added to a 10% polyvinyl alcohol aqueous solution for granulation; wherein the amount of the polyvinyl alcohol aqueous solution is determined according to the weight ratio of the nano-powder to the polyvinyl alcohol of 0.5:0.4.

[0077] f. Forming: NZCSF nanoparticles were pressed into annular samples (Ф18mm×Ф8mm×h5mm) by a mold under 20MP pressure for 1min, and into sheet samples (R10mm×h5mm) under 10MP pressure for 1min; the annular samples were used for the measurement of magnetic permeability and magnetic loss. The sheet samples were used for the measurement of X-ray diffraction patterns, dielectric constant, electrical loss, resistivity, sintered density, saturation magnetization and coercivity.

[0078] g. Sintering: Sinter the sample at 1150°C for 4 hours to obtain ferrite material.

[0079] The scandium-substituted nickel-zinc-cobalt ferrite soft magnetic material prepared in this embodiment has the general formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where x = 0.025.

[0080] Example 2

[0081] A method for preparing a scandium-doped nickel-zinc-cobalt ferrite soft magnetic material comprises the following steps:

[0082] 1) Ingredients

[0083] Analytical pure Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, Co(NO3) 2,Sc(NO3)3·6H2O and Fe(NO3)3·9H2O are used as raw materials, according to the chemical formula Ni 0.5 Zn 0.4 Co 0.1 Sc 0.050 Fe 1.950 O4 weighs the ingredients.

[0084] 2) Preparation

[0085] a. Preparation of wet gel precursor: Ni 0.5 Zn 0.4 Co 0.1 Sc 0.050 Fe 1.950 O4 dissolves nitrate in deionized water and mixes thoroughly to form a solution with a concentration of 0.15 mol / L; adds citric acid in a molar ratio of citric acid to nitrate in 3 to the prepared solution, then seals it, and then stirs it magnetically at 80°C for 4 hours to obtain a clear brown-green precursor solution; after cooling the precursor solution to room temperature, adds ammonia water to it and adjusts its pH value to 7;

[0086] Subsequently, the scandium-doped nickel-zinc-cobalt ferrite soft magnetic material was prepared according to steps b to g in Example 1.

[0087] The scandium-substituted nickel-zinc-cobalt ferrite soft magnetic material prepared in this embodiment has the general formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where x = 0.050.

[0088] Example 3

[0089] A method for preparing a scandium-doped nickel-zinc-cobalt ferrite soft magnetic material comprises the following steps:

[0090] 1) Ingredients

[0091] Analytical pure Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, Co(NO3) 2, Sc(NO3)3·6H2O and Fe(NO3)3·9H2O are used as raw materials, according to the chemical formula Ni 0.5 Zn 0.4 Co 0.1 Sc 0.075 Fe 1.925 O4 weighs the ingredients.

[0092] 2) Preparation

[0093] a. Preparation of wet gel precursor: Ni 0.5Zn 0.4 Co 0.1 Sc 0.075 Fe 1.925 O4 dissolves nitrate in deionized water and mixes thoroughly to form a solution with a concentration of 0.15 mol / L; adds citric acid in a molar ratio of citric acid to nitrate in 3 to the prepared solution, then seals it, and then stirs it magnetically at 80°C for 4 hours to obtain a clear brown-green precursor solution; after cooling the precursor solution to room temperature, adds ammonia water to it and adjusts its pH value to 7;

[0094] Subsequently, the scandium-doped nickel-zinc-cobalt ferrite soft magnetic material was prepared according to steps b to g in Example 1.

[0095] The scandium-substituted nickel-zinc-cobalt ferrite soft magnetic material prepared in this embodiment has the general formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where x = 0.075.

[0096] Example 4

[0097] A method for preparing a scandium-doped nickel-zinc-cobalt ferrite soft magnetic material comprises the following steps:

[0098] 1) Ingredients

[0099] Analytical pure Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, Co(NO3) 2, Sc(NO3)3·6H2O and Fe(NO3)3·9H2O are used as raw materials, according to the chemical formula Ni 0.5 Zn 0.4 Co 0.1 Sc 0.100 Fe 1.900 O4 weighs the ingredients.

[0100] 2) Preparation

[0101] a. Preparation of wet gel precursor: Ni 0.5 Zn 0.4 Co 0.1 Sc 0.100 Fe 1.900 O4 dissolves nitrate in deionized water and mixes thoroughly to form a solution with a concentration of 0.15 mol / L; adds citric acid in a molar ratio of citric acid to nitrate in 3 to the prepared solution, then seals it, and then stirs it magnetically at 80°C for 4 hours to obtain a clear brown-green precursor solution; after cooling the precursor solution to room temperature, adds ammonia water to it and adjusts its pH value to 7;

[0102] Subsequently, the scandium-doped nickel-zinc-cobalt ferrite soft magnetic material was prepared according to steps b to g in Example 1.

[0103] The scandium-substituted nickel-zinc-cobalt ferrite soft magnetic material prepared in this embodiment has the general formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where x = 0.100.

[0104] Comparative Example 1

[0105] A method for preparing a scandium-doped nickel-zinc-cobalt ferrite soft magnetic material comprises the following steps:

[0106] 1) Ingredients

[0107] Analytical pure Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, Co(NO3)2 and Fe(NO3)3·9H2O were used as raw materials. 0.5 Zn 0.4 Co 0.1 Weigh and mix Fe2O4.

[0108] 2) Preparation

[0109] a. Preparation of wet gel precursor: Ni 0.5 Zn 0.4 Co 0.1 Fe2O4 dissolves nitrate in deionized water and mixes thoroughly to form a solution with a concentration of 0.15 mol / L; adds citric acid in a molar ratio of citric acid to nitrate of 3 to the prepared solution, and then seals it, and then stirs it magnetically at 80°C for 4 hours to obtain a clear brown-green precursor solution; after cooling the precursor solution to room temperature, ammonia water is added thereto to adjust its pH value to 7;

[0110] Subsequently, the scandium-doped nickel-zinc-cobalt ferrite soft magnetic material was prepared according to steps b to g in Example 1.

[0111] The scandium-substituted nickel-zinc-cobalt ferrite soft magnetic material prepared in this comparative example has the general formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where x=0.

[0112] Comparative Example 2

[0113] Based on Example 2, only step d is changed, and the rest of the process is the same as Example 2.

[0114] Step d is: ball milling: placing the obtained nano-scale powder into a ball milling jar for ball milling; after 11 hours of ball milling, NZCSF ferrite powder is obtained;

[0115] The scandium-substituted nickel-zinc-cobalt ferrite soft magnetic material prepared in this comparative example has the general formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where x = 0.050.

[0116] Comparative Example 3

[0117] Based on Example 2, only step d is changed, and the rest of the process is the same as Example 2.

[0118] Step d is: ball milling: putting the obtained nano-scale powder and CaCO3 into a ball mill for ball milling; after 11 hours of ball milling, NZCSF ferrite powder is obtained; the amount of CaCO3 is added according to the weight ratio of nano-scale powder to CaCO3 of 18:2.

[0119] The scandium-substituted nickel-zinc-cobalt ferrite soft magnetic material prepared in this comparative example has the general formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where x = 0.050.

[0120] Comparative Example 4

[0121] Based on Example 2, only step d is changed, and the rest of the process is the same as Example 2.

[0122] Step d is: ball milling: put the obtained nano-scale powder and SiO2 into a ball mill for ball milling; after 11 hours of ball milling, NZCSF ferrite powder is obtained; the amount of SiO2 used is 18g:2g according to the weight ratio of nano-scale powder to SiO2.

[0123] The scandium-substituted nickel-zinc-cobalt ferrite soft magnetic material prepared in this comparative example has the general formula: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4, where x = 0.050.

[0124] The scandium-substituted nickel-zinc-cobalt ferrite soft magnetic materials obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were tested, and the sintered density d b , initial magnetic permeability μ iThe test results of the frequency conversion coefficient (1MHz), coercive force Hc, saturation magnetization MS and DC resistivity ρ are shown in Tables 1 and 2.

[0125] The detection method of the present invention is as follows:

[0126] 1. The diameter and thickness of the sintered samples were measured using a micrometer caliper, and the mass was weighed using a high-precision electronic balance (FA2104J) with an accuracy of 0.1 mg.

[0127] 2. The initial magnetic permeability of the sintered samples was measured by Agilent HP4291B.

[0128] 3. The coercive force of the sintered samples was obtained by measuring the hysteresis loop using a Lake Shore 8604 vibrating sample magnetometer in a magnetic field range of -10000 to +10000 Oe at room temperature.

[0129] 4. The Lake Shore 8604 vibrating sample magnetometer can simultaneously measure the saturation magnetization.

[0130] 5. The DC resistivity of the sintered samples was measured by a Keithley 6517B high resistance meter in the temperature range of 25 to 250 °C.

[0131] Table 1

[0132]

[0133] Table 2

[0134]

[0135] Compared with Comparative Example 1, Examples 1 to 4 show that by adding Sc 3+ , which affects the original ion distribution of nickel-zinc-cobalt ferrite, changes the grain diameter of nickel-zinc-cobalt ferrite, and enhances the saturation magnetization intensity of nickel-zinc-cobalt ferrite soft magnetic materials.

[0136] As can be seen from Tables 1 to 2, the sintering density of the nickel-zinc-cobalt ferrite prepared by the present invention using the rare earth element scandium as a dopant and adding a variety of additives increases, the initial magnetic permeability increases, and the resistivity and saturation magnetization reach the maximum value in Example 2. Various properties are greatly improved compared with Comparative Examples 1 to 4.

Claims

1. Scandium-doped nickel-zinc-cobalt ferrite, characterized in that Its molecular formula is: Ni 0.5 Zn 0.4 Co 0.1 Sc x Fe 2-x O4; wherein 0<x≤0.1, the ferrite is prepared by a method comprising the following steps: a. Prepare a wet gel precursor: mix nickel salt, zinc salt, cobalt salt, iron salt, scandium salt and water, add citric acid after dissolving, stir and react at 70-90° C. for 3-6 h, and then adjust the pH value to 6.5-7.5 to obtain a wet gel precursor; b. Preparing a dry gel precursor: drying the wet gel precursor to obtain a dry gel precursor; c. Self-propagating combustion reaction: Use an igniter to ignite the dry gel precursor, which self-propagates into nano-scale powder; d. Ball milling: mixing the nano-sized powder with the additive and then ball milling to obtain a ball mill material; wherein the additive is a mixture of CaCO3 and SiO2; e. Granulation: After the ball mill is dried, polyvinyl alcohol is added to granulate; f. Blank making: the powder after granulation is pressed into blanks; g. Sintering: Sinter the blank at 1100-1200°C for 2-6 hours to obtain scandium-doped nickel-zinc-cobalt ferrite.

2. The scandium-doped nickel-zinc-cobalt ferrite according to claim 1, characterized in that: 0.025≤x≤0.1。 3. The scandium-doped nickel-zinc-cobalt ferrite according to claim 1, characterized in that: x=0.025, 0.05, 0.075 or 0.

1.

4. A method for preparing scandium-doped nickel-zinc-cobalt ferrite, characterized in that: The following steps are involved: a. Prepare a wet gel precursor: mix nickel salt, zinc salt, cobalt salt, iron salt, scandium salt and water, add citric acid after dissolving, stir and react at 70-90° C. for 3-6 h, and then adjust the pH value to 6.5-7.5 to obtain a wet gel precursor; b. Preparing a dry gel precursor: drying the wet gel precursor to obtain a dry gel precursor; c. Self-propagating combustion reaction: Use an igniter to ignite the dry gel precursor, which self-propagates into nano-scale powder; d. Ball milling: mixing the nano-sized powder with the additive and then ball milling to obtain a ball mill material; wherein the additive is a mixture of CaCO3 and SiO2; e. Granulation: After the ball mill is dried, polyvinyl alcohol is added to granulate; f. Blank making: the powder after granulation is pressed into blanks; g. Sintering: Sinter the blank at 1100-1200°C for 2-6 hours to obtain scandium-doped nickel-zinc-cobalt ferrite.

5. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 4, characterized in that: In step a, the nickel salt is nickel nitrate, the zinc salt is zinc nitrate, the cobalt salt is cobalt nitrate, the iron salt is iron nitrate, and the scandium salt is scandium nitrate.

6. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 4 or 5, characterized in that: In step a: the molar ratio of nickel salt, zinc salt, cobalt salt, iron salt and scandium salt is 3-5:2-4:0.7-0.9:15-17:0.15-0.

9.

7. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 6, characterized in that: The molar ratio of nickel salt, zinc salt, cobalt salt, iron salt and scandium salt is 3~5:2~4:0.7~0.9:15~17:0.7~0.

9.

8. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 4 or 5, characterized in that: In step a, the amount of citric acid added is 2 to 4 times the sum of the amounts of nickel salt, zinc salt, cobalt salt, iron salt and scandium salt.

9. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 8, characterized in that: The amount of citric acid added is 3 times the sum of the amounts of nickel salt, zinc salt, cobalt salt, iron salt and scandium salt.

10. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 4 or 5, characterized in that: In step d, the weight ratio of CaCO3 to SiO2 is 0.4~1.6:0.5~1.

2.

11. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 4 or 5, characterized in that: In step d, CaCO3 and SiO2 are added in a ratio of 17-21: 0.4-1.6: 0.5-1.2 of the weight ratio of nano-powder, CaCO3 and SiO2.

12. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 4, characterized in that: In step a, the reaction was stirred at 80° C. for 4 h, and then the pH value was adjusted to 7; In step b, the drying temperature is 70°C to 90°C; In step c, the ignition agent is alcohol; In step d, the ball milling time is 9 to 18 hours; In step e, the polyvinyl alcohol is a polyvinyl alcohol aqueous solution; In step f, the pressing pressure is 5 to 20 MPa, and the pressing time is 0.5 to 2 min; In step g, the blank is sintered at 1150° C. for 4 h.

13. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 12, characterized in that: The concentration of the polyvinyl alcohol aqueous solution is 6 wt% to 12 wt%, and the amount of the polyvinyl alcohol aqueous solution is determined according to the weight ratio of the nano-powder to the polyvinyl alcohol of 0.3 to 0.7: 0.2 to 0.

5.

14. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 12, characterized in that: In step f, the pressing pressure is 10 MPa and the pressing time is 1 min.

15. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 12, characterized in that: In step b, the drying temperature is 80°C.

16. The method for preparing scandium-doped nickel-zinc-cobalt ferrite according to claim 12, characterized in that: In step d, the ball milling time is 11 h.

Citation Information

Patent Citations

  • Yttrium-doped nickel-zinc-cobalt ferrite and preparation method thereof

    CN112159219A